Cambios estacionales del mantillo en el suelo de un bosque tropical caducifolio y uno subcaducifolio en Chamela, Jalisco, México - Martínez Yrizar, Angelina; Sarukhán, José (Instituto de Ecología, A.C., 1993)
The present study reports on the seasonal variation of standing crop iitter in a tropical deciduous and a semideciduous forest in Chamela, Jalisco, México. The amount of surface Iitter was, on average, higher in the semideciduous forest, where the turnover rate of standing crop Iitter was faster. The temporal variation in the mean amount of standing crop Iitter exhibited a marked seasonal pattern. Surface Iitter tended to accumulate during the dry season when litterfall was at its máximum, and decreased considerably was a result of decomposition during the rainy season.